CULTURAL DIPLOMACY AS AN INSTRUMENT OF THE STATE'S "SOFT POWER" (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Cultural diplomacy is a phenomenon that is increasingly mentioned in the foreign policy strategies of modern states and is becoming one of the leading tools in the implementation of foreign policy. Before exploring the effectiveness of using cultural diplomacy methods, it is considered appropriate to consider the definition and purpose of this phenomenon. Today it is not considered possible to assert that in scientific and political discourse there is a unified approach to defining the phenomenon of cultural diplomacy. Many of the studies, academic papers and regulations presented and analyzed in this chapter use a variety of terminology: “cultural diplomacy”, “cultural policy”, “external cultural policy”, “external cultural activities”, “soft power” and some others. Often the listed concepts are interchangeable and are used by some researchers and practitioners as synonyms.